Effect of Particle Size Distribution, pH, and Na+ Concentration on the Chemical Mechanical Polishing of Sapphire and 4H-SiC (0001). (1st April 2022) - Wang, Weilei; Xu, Qiufeng; Liu, Weili; Song, Zhitang
Abstract : As two typical representatives of super-hard materials, sapphire and silicon carbide, their processing has always been a hot spot. Chemical mechanical polishing (CMP) technology is the only way to achieve global planarization, and it has also become one of the most important processes for precision machining of sapphire and silicon carbide. This paper introduced the relationship between the removal rate and surface roughness of sapphire and 4H-SiC (0001) and the size distribution and pH of alumina slurry. More importantly, this paper explored the negative effect of Na + on the removal rate of alumina-based sapphire polishing slurry, and the more negative effect of Na + on the removal rate of alumina-based silicon carbide polishing slurry and the surface state of SiC(0001). At the end of the article, the polishing mechanism of sapphire with alumina as a brasive was given.